A Case of Left Retroexternal Iliac Artery Megaureter Associated with Additional Renal and Vascular Congenital Anomalies - Amin A. Karadaghy; Matthew T. Bell; Daniel T. Daly; Yun Tan (Case Reports in Urology)
Introduction. A number of rare anatomical anomalies, including retroexternal iliac ureter, extrarenal calyces (ERCs), and vascular anomalies, were observed in a 96-year-old female cadaver during a routine dissection. Description. A markedly dilated left extrarenal pelvis (ERP) with a diameter of 3.15 cm was noticed. Three major calyces were found outside of the normal-sized left kidney. The abdominal aorta (AA), instead of normal bifurcation, branched to the right common, left external, and left internal iliac arteries. The median sacral artery was a direct branch from the right common iliac artery. No hydronephrosis was observed on the affected side, and no urinary tract anomalies were observed on the right side. Significance. The retroiliac megaureter is a rare congenital anomaly, with fewer than 25 cases reported to date. Additionally, the ERCs are amongst the rarest anomalies of the renal collecting system. Further, the current case is one of few reported cases where the particular branching pattern of the AA was observed. The combination of such anatomical anomalies is rare, and the relationship between them is unclear. Common clinical manifestations of retroiliac ureters are the results of ureteric obstruction, hydronephrosis, and secondary infection. Precise knowledge of anomalies of the kidney and urinary tract can help radiologists and surgeons make a definitive diagnosis and prevent inadvertent injury during surgery.